Influence of Brand Love on the Purchase Intention of Dairy Beverages, Machala, Ecuador (Journal SCIENCEVOLUTION, 2025)
The purpose of this research is to analyze the relationship between Brand Love, Innovation, Electronic Word-of-Mouth (e-WOM), and Purchase Intention in the dairy beverage sector in the city of Machala. A quantitative approach was employed, with a non-experimental, cross-sectional, and correlational design. The sample consisted of 330 individuals aged 18 to 45, selected through convenience sampling. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM) via SmartPLS software. The results revealed that Brand Love positively influences Purchase Intention, the perception of Innovation, and the willingness to recommend the brand. Additionally, Innovation was found to have a direct effect on Purchase Intention. However, e-WOM did not exhibit a significant relationship with Purchase Intention, suggesting it does not always directly influence consumer decisions. It is concluded that emotions play a fundamental role in consumption decisions. Companies that emotionally connect with customers, innovate, and communicate with closeness achieve success in the current market. This study provides a practical and useful guide for brands seeking to position themselves in the local environment.
Keywords: Brand Love; Purchase intention; Innovation; e-WOM; Consumer